Vegetation cover and plant diversity on cold climate green roofs - Lönnqvist, Joel; Blecken, Godecke-Tobias; Viklander, Maria (Zenodo, 2020)
Both vegetation abundances and community compositions play important roles for the functions of green roofs (e.g. stormwater retention, habitat provision, aesthetic appearance). However, green roof vegetation can change significantly over time, which may consequently affect the functions related to them. This study investigated vascular plant covers and species compositions on 41 roof sections located in Sweden's subarctic and continental climate zones. For the roof sections with a known originally intended vascular plant composition (n=32), on average 24±9% of the intended species were present in surveys while unintended species made up 69±3% of the the species found. The Intended species dominated plant cover (93±3%) and Sedum acre (58±36% cover) was the most commonly found species. As revealed in previous studies, substrate depth had a positive relationship with plant cover and species richness. The vascular plant cover of the roofs in this study was not related to species richness as hypothesized but instead had a significant negative correlation with moss cover. The results in this study emphasize the importance of substrate depth for both plant abundance and species diversity, and that even in a cold climate, colonising unintended species can have a great contribution to the species richness of green roofs. However, since most colonising species formed sparse cover on the roofs, their potential benefit to green roof functions that benefit from a dense vegetation cover (e.g. stormwater management and thermal performance) could be limited while the intended vegetation performs these functions more effectively. Funding provided by: Svenska Forskningsrådet Formas Crossref Funder Registry ID: http://dx.doi.org/10.13039/501100001862 Award Number: 2014-00854